Default and Termination of Contract: A comparative Study between Indonesia and The United Kingdom - Akhmad Budi Cahyono (Universitas Airlangga, 2020)
Default is something that often occurs in contractual relationship. It can be not perform its obligations in the contract in all or in a part, performing its obligations but not in accordance with was agreed, performing its obligations but not in time, and performing something that is prohibited in the contract. Due to default, the injured party may claim compensation and / or terminate the contract. The problem is, the Indonesian Civil Code does not specify how a contract can be terminated in case of default. Therefore, it is necessary to conduct a comparative study in other countries in terms of how a default can terminate the contract. The British which adopt common law tradition where jurisprudence is the main source of law is the right choice for conducting comparative studies. Countries with common law traditions have detailed legal rules based on jurisprudence. As in Indonesia, according to British contract law, defaults also can terminate the contract. However, unlike in Indonesia, according to British contract law, termination due to a default is only allowed in the event that the default is very serious. The very serious forms of default will be elaborated and become a part of the discussion in this paper.